Use of Blockchain technology for the exchange and secure transmission of medical images in the cloud: Systematic Review with Bibliometric Analysis - Lizama, Maria Guzman; Huesa, Jair; Claudio, Brian Meneses (Universitas Pendidikan Indonesia (UPI), 2024)
The research questions focused on emerging challenges, solutions, approaches, encryption methods, architectures, and opportunities related to blockchain technology in medical image sharing, and a total of 17 relevant articles were selected from the Scopus database for analysis. The increasing adoption of cloud computing environments in the medical field has raised concerns about security and privacy risks. Within these concerns, problems were identified regarding secure data storage, since centralized storage systems in the cloud mostly lack security effectiveness. Blockchain technology offers a decentralized and secure infrastructure to address these problems. However, a systematic review is needed to identify the strengths and limitations of this technology in this context, therefore the objective of this review is to provide a critical and updated view of the security aspects of the use of blockchain technology in the exchange of medical images in the cloud. The proposed solutions included practical byzantine fault tolerance algorithms, homomorphic encryption, and the integration of smart contracts, among others. In conclusion, this review provides insight into the application of blockchain technology for the secure sharing of medical images in the cloud and identifies key technologies, challenges, solutions, and opportunities in the field.